Non‐Invasive Monitoring of Osteogenic Differentiation on Microtissue Arrays under Physiological Conditions Using Scanning Electrochemical Microscopy. Issue 9 (30th July 2014) - Sridhar, Adithya; van den Berg, Albert; Le Gac, Séverine
Abstract In this paper, we present a non‐invasive assay using scanning electrochemical microscopy (SECM) for detecting osteogenic differentiation at physiological conditions (pH 7.5) on arrays of C2C12 microtissues. Upon exposure to bone morphogenic protein 2 (BMP‐2), C2C12 microtissues differentiate and express alkaline phosphatase (ALP), which is indirectly detected through an enzymatic assay producing an electroactive species. The latter is detected using SECM by scanning at constant height over live microtissues at physiological pH (7.5) as well as more alkaline pH (8.5). As a control, expression of ALP is confirmed using a standard colorimetric assay. Detecting differentiation on live samples at physiological conditions represents a significant improvement for continuous monitoring of tissue differentiation or further use of the microtissues for, e.g., regenerative medicine.